Unique Equivalence Scales: Estimation and Implications for Distributional Analysis - Johnson, David S.; Garner, Thesia I. (Journal of Income Distribution®, 1995)
Equivalence sales are used to adjust income by family size to obtain income distribution measures. Recently, the concept of equivalence scale elasticity has been introduced to characterize the effect that scales have on distribution measures. We produce utility-based equivalence scales that have the property of constant elasticity. By assuming a particular functional form for the scales and that the scales are independent of the base level of utility, we obtain unique equivalence scales. In contrast to previous estimates of utility-based scales, we do not restrict our sample to particular family types. We determine price-dependant scales by estimating a characteristic-dependent almost ideal demand system using quarterly expenditure data from the US Consumer Expenditure Survey and price indices from the US Consumer Price Index. We use our scales and those implicit in the US official poverty thresholds to adjust expenditures and show that these scales have similar effects on inequality measures.